D’Bridal Boutique website and online customer reservation system / Aziatul Azna Mohd Isa - Mohd Isa, Aziatul Azna (2012)
This research is about designed of D’Bridal Boutique Website and Online Customer Reservation System. Since people nowadays are educated, they chose the easy way to find the information about the product or services through online system. The planning of D’Bridal Boutique is to venture into online digital area to advertise their product and service so that more people can easily look about the business for themselves the design and package that they want. The objectives of the project are to identify the reservation problems of the D’Bridal Boutique and help them to market D’Bridal Boutique and advertise that presence in the online bridal package community in Malaysia, to develop a website for D’Bridal Boutique using User-Centered Design (UCD) in combination with Software Development Life Cycle (SDLC) then to evaluate the usability and acceptance level of user towards the D’Bridal Boutique website. The research methodology used during the development of this system is an adapted from User-Centered Design (UCD) and Software Development Life Cycle (SDLC). As a conclusion, the entire three objectives have been achieved. User-Centered Design (UCD) in combination with Software Development Life Cycle (SDLC) is a method that can help developer or designer to produce a website that easy to use by users indirectly meet the user needs. That has been proven by this D’Bridal Boutique website.